The Net That We Could Not Fly By Portals of Discovery. - Voss-Hoynes, Kurt (James Joyce Literary Supplement)
The article reports on the catastrophic failure suffered by the computer system of "James Joyce Literary Supplement" and various corrections to errors in various articles in the supplement.